Anticoagulant effects of rivaroxaban, prednisone, alone and in combination, in healthy dogs - Paige M. Hafner; Andrew J. Mackin; Robert W. Wills; Marjory B. Brooks; John M. Thomason (Journal of Veterinary Internal Medicine, 2022)
Abstract Background The potential effects of glucocorticoid administration on rivaroxaban's anticoagulant bioactivity in dogs, and an appropriate rivaroxaban dosage regimen for dogs receiving glucocorticoid therapy are unknown. Hypothesis/Objectives The objective was to determine whether glucocorticoid administration influences the anticoagulant effects of rivaroxaban in healthy dogs. We hypothesized that administration of rivaroxaban and prednisone would reduce the anticoagulant intensity compared with rivaroxaban alone. Animals Nine healthy dogs. Methods Randomized, cross‐over study. Dogs were administered prednisone (2 mg/kg, PO, q24h), rivaroxaban (1.5 mg/kg, PO, q24h), or prednisone and rivaroxaban, and the coagulation status was evaluated using prothrombin time (PT), and rivaroxaban‐calibrated anti‐Xa activity (RIVA, results were log10 transformed for analysis), before drug administration and on days 2, 4, and 8. Linear mixed models and correlation were used to evaluate associations in variables (P < .05 was considered significant). Results There were no differences in RIVA results for the rivaroxaban and prednisone/rivaroxaban groups on day 8 (P = .599, median 87 [range 45‐156] to 167 [56‐333], respectively, median difference 90 ng/mL [95% CI:87.3‐161.8]) There was a strong correlation between RIVA and PT results when days 2, 4, and 8 were combined (r = .846, P < .001), and increased during drug administration, day 2 (r = .810, P < .001), day 4 (r = .863, P < .001), and day 8 (r = .885, P < .001). Conclusions and Clinical Importance Clotting times in the PT correlate with rivaroxaban levels and may prove useful for drug monitoring. Prednisone administration had no apparent influence on the anticoagulant effects of rivaroxaban in healthy dogs, suggesting that combined therapy will not require dosage adjustments.